Fotografia: artefato, afetos e aprendizagens no ambiente digital - Ramos, Nandra Imiane (2022)
The research "Photography: artifact, affect and learning in the digital environment" has as its object of investigation the photographs produced in the digital environment, specifically in the social network Instagram and the way they are conveyed as affective devices of contemporary looks, having been guided by the following question-problem: how can photography act as a learning and affective device in the mediation of seeing during the pandemic? For this, I gathered a group of ten participants to follow them netnographically (KOZINETS, 2010; FERRAZ, 2019) and produce cartographies (BARROS; KASTRUP, 2009) regarding their personal relationships with photography. Thus, the data collection of this qualitative research was carried out with members of the UFG community and over 18 years old, aiming to perform a netnographic follow-up of their profiles on Instagram for a month. Thus, through an informal learning environment (LIB NEO, 2010; GOHN, 2006), conversations via Google Meet took place about the respective profiles on the social network, their relationships with photography and social interactions. Thus, with the subjects' own photographs and the affections cited during the meetings, cartographies were produced in order to make explicit the relationships with images during this pandemic period. The main objectives are: to link photography to affects, both as resources that enable the externalization of subjectivities; to map the affects exposed in the photographs, through the affective cartography methodology; to understand how photography operates in the deconstruction of the hegemony of seeing, and investigate how photography, through cultural pedagogies, operates as a learning tool in the digital environment. Therefore, the main contribution with this line of research is to suggest a study about decentralized learning, related to informal education and cultural pedagogies (ANDRADE, COSTA; 2015), which move beyond formal educational spaces, continuously throughout life. Including through photographic images in the digital environment, which constitute and form visual experiences about perceptions of the world. Thus, it is possible to propose that the main contribution to the visual arts and culture field is supporting the construction of new knowledge, proposing a critical and historical reflection on photographs and contemporary looks, under the pandemic context. Since reality also shapes sociocultural experiences and carries affections to the relationships with image. And, thus, open knowledges that arise from everyday learning, understanding that the different formats of photography are part of Arts.